Réécrire Molière en Turquie à l'Âge des réformes: Seconde moitié du XIXe siècle - Williams-Kurt, Çiğdem (My University, 2015)
In the second half of the nineteenth century, Molière's comedies were seen as a fertile source of material for Ottoman playwrights eager to bring new ideas to the popular dramatic arts and to create a new form of national theater. Ottoman translators who translated or adapted Molière's theater into Ottoman Turkish and who rewrote the theater into their native language brought the classical French playwright to the general public. Therefore they started an historical period that we will refer to as the « Age of Translation » (1869-1882). There were two primary ways in which French theater was transmitted to the theater-going public: Some plays were translated and adapted into local languages using French themes and stories, and other plays were performed directly in the original French. These two different modes through which Molière influenced nineteenth century Ottoman theater form the dominant two axes of this dissertation. This dissertation proposes to write a new perspective on the history of modern Turkish theater, to describe the debates surrounding the first establishment of a « national » Ottoman theater, to show how the growing popularity of Molière changed the themes and style of popular Ottoman theater, to show the effect of French theater celebrities coming to what was a lively and cosmopolitan Istanbul, and finally how the conflicts and similarities between Ottoman and French theater were reconciled with one another. The principle questions which guide us in our research are the following: Who were the viewing public who attended Molière’s plays, whether performed in Turkish or French? What were the images left in the mind's eye of the audience during these plays? Why did Ottoman translators and men of the theater particularly single out Molière for translation during this period? What are the modern implications of the importation process of Molière’s plays into the Ottoman Empire of the nineteenth century?

Molière’in komedileri, on dokuzuncu yüzyılın ikinci yarısında, halk tiyatrosu biçimlerini yenilemeyi ve böylece yeni bir milli tiyatro kurmayı hedefleyen Osmanlılar için verimli bir kaynağa dönüşür. Molière tiyatrosunu Osmanlı Türkçesine çeviren ya da uyarlayan, bu tiyatroyu kendi dilinde yeniden yazan Osmanlı çevirmenleri, klasik Fransız tiyatro yazarını yerel seyirciye götürür ve bizim bu çalışmada « Çeviriler Çağı » (1869-1882) olarak adlandırdığımız dönemi açar. On dokuzuncu yüzyılda Fransız tiyatro repertuvarının yurtdışına yayılmasını sağlayan iki kol (özgün/kaynak dillerinde bir yerden bir yere taşınan oyunlar ve dönemin çok tutulan Fransız oyunlarının çevirileri ya da çeşitli uyarlamaları) bu çalışmanın iki ana eksenini oluşturur. Bu çalışma, Molière tiyatrosunun Reformlar Çağı’nda Osmanlı İmparatorluğu’na taşınma sürecini bütünlüğü ve karmaşıklığı içinde incelemeyi amaçlar. Aynı zamanda, modern Türk tiyatrosu tarihini, « milli » bir karakter taşıyan ilk Osmanlı tiyatrosunun kurulmasını takip eden tartışmaları, halk tiyatrosunun farklı biçimlerinin Molière tiyatrosunun Osmanlı başkentinde yakaladığı başarı karşısında nasıl değişime uğradığını, dönemin Fransız tiyatro yıldızlarının kültürel açıdan son derece canlı ve kozmopolit olan İstanbul'a yaptığı büyük turneleri, son olarak da Osmanlı ve Fransız tiyatro adamları arasındaki çatışma ve uzlaşmaları yeni bir bakış açısıyla kaleme almayı hedefler. Araştırmamızda bizi yönlendiren belli başlı sorular şunlardır: İstanbul’da Molière’i Fransızca ya da Türkçe olarak izleyenler kimlerdir? Osmanlı seyircisinin gözünde farklı Molière imgeleri var mıdır? Osmanlı çevirmenleri ve tiyatro adamları bu dönemde neden Molière’e yönelmiştir? Molière tiyatrosunun on dokuzuncu yüzyılın ikinci yarısında Osmanlı İmparatorluğu'na taşınmasının günümüze etkileri nelerdir?
Reformlar Çağı’nda Türkiye’de Molière’in yeniden yazımı (19. yüzyılın ikinci yarısı)
Tez (Doktora) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2015
Keywords: Molière; Osmanlı-Türk tiyatrosu; Tiyatro çevirisi; Yeniden yazım; Tiyatro turneleri; Karşılaştırmalı edebiyat; Ottoman-Turkish theater; Theater translation; Comparative literature; Rewriting; Tours